Supplementing sows with the leucine metabolite beta-hydroxy-beta-methylbutyrate and vitamin D3 improves piglet birth weights that may lead to increased weaning weights - Fuller, John C.; Rathmacher, John A.; Castro, Fabricio Faleiros; Chaves, Rhuan Filipe; Mohr, Mike (Frontiers in Animal Science, 2022)
Previous university studies demonstrated that supplementing sows with calcium beta-hydroxy-beta-methylbutyrate (CaHMB) in late gestation and/or lactation improved piglet weights through weaning. Two studies were conducted at commercial farrowing operations to test if the results would translate to commercial operations. Sows in both trials were randomized to receive either 3 g/day CaHMB plus 500 IU/day vitamin D3 (HMB/D) or a calcium carbonate containing control top-dressed to the feed from day 104 of gestation through weaning. Sows were randomly assigned to either HMB/D (n = 41 trial 1 and n = 26 trial 2) or control (n = 46 trial 1 and n = 26 trial 2). Data were analyzed using a general linear model with main effects of group, treatment, and group by treatment interaction. Treatment with HMB/D had no effect on sow weights, lactational weight loss, and stillborn or mummified piglets. In trial 1, the control group had an increased number of live born piglets, which at 24 h tended to be greater, and no difference in liveborn or 24-h piglet numbers was seen in trial 2. In trial 1, HMB/D increased piglet live birth (P < 0.03) and 24-h weights (1,490 ± 30.1 vs. 1,390 ± 28.8 g in HMB/D and control piglets, respectively, P < 0.02). Farm practices were to equalize piglet numbers across sows by cross-fostering. After cross-fostering, the 24-h average piglet weights were not different, and further advantages to supplementation were not observed (P = 0.21). In trial 2, birth and 24-h weights of the piglets from HMB/D-supplemented sows were increased (P < 0.0001). Piglets from sows supplemented with HMB/D were 9.7% heavier at birth and 9.2% heavier at 24 h (1,549 ± 22.0 and 1,419 ± 21.2 in HMB/D and control, respectively). A difference was observed in weaning age (P < 0.0001), and weaning weights were adjusted to 21-day weights (5,426 ± 103.5 and 5,205 ± 99.5 for HMB/D and control piglets, respectively, P = 0.12). Analysis by group showed that HMB/D tended to increase weaning weights in younger sows (second and third parity), 5,432 ± 150.7 and 5,074 ± 142.7 in HMB/D and control piglets, respectively (P < 0.09). In conclusion, these results agree with previous university studies demonstrating that CaHMB supplementation increased early piglet weights with a tendency to improve weaning weights.